Analisa Pemahaman Discharge Planning dengan Tingkat Kepatuhan Pasien Gagal Ginjal Kronik (GGK) Dalam Menjalani Terapi Hemodialisis Di Rumah Sakit Islam Jemursari Surabaya - Maslakha, Lilik; Heris Santy, Wesiana (Jurnal Ilmiah Kesehatan, 2015)
Hemodialysis is one of renal replacement therapy in patients with CRF, one of the problems that led to the failure of hemodialysis is the issue of compliance. Therefore it takes the role of health workers in providing understanding of discharge planning for continuity of care in achieving the quality of life of patients. The study aims to determine the relationship of understanding of discharge planning with the level of compliance in the CRF patients undergoing hemodialysis therapy in RSI Jemursari Surabaya. Analytical research method with cross sectional design. The population is all patients with chronic renal failure undergoing hemodialysis for 70 people and a large sample of 59 respondents. Systematic sampling with sampling techniques. The instrument has it under the sheet questionnaires, and then analyzed by Spearman correlation test using SPSS 16.0 can for Windows. The results showed that a large majority of the 59 respondents 35 (59.3%) a good understanding of discharge planning, compliance levels in CRF patients undergoing hemodialysis therapy most of the 30 (50.8%). With the relationship of discharge planning with the level of compliance in the CRF patients undergoing hemodialysis therapy, it is expected that health workers can provide clear information to patients, in the form of discharge planning which is in good order and improve the quality of interaction to the family and the patient.